2020
DOI: 10.9734/ajaees/2020/v38i630360
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rural Households’ Food Insecurity in Ekiti State, Nigeria

Abstract: Attaining food security is one of the targets of the Sustainable Development Goals. Despite the various efforts made by governments, food insecurity continues to be a major developmental problem across the globe. Research shows that food production in Nigeria is increasing at a rate of less than 2.0% while the population growth rate is estimated to be increasing at 2.5% per annum. Therefore, this study was carried out to assess rural households’ food insecurity in Ekiti state, Nigeria. Descriptive stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…A similar high prevalence of food insecurity was reported across the country during this pandemic [20]. In this study, the finding is much higher than what was reported from studies conducted in Ekiti before the pandemic: 68.3% by Toluwalase et al [24] and 64.7% by Oladeji [25]. This finding justifies the concerns that the WHO had on the potential impact of COVID-19 on the food and nutrition situation of the vulnerable groups, especially in developing countries [26].…”
Section: Resultssupporting
confidence: 77%
“…A similar high prevalence of food insecurity was reported across the country during this pandemic [20]. In this study, the finding is much higher than what was reported from studies conducted in Ekiti before the pandemic: 68.3% by Toluwalase et al [24] and 64.7% by Oladeji [25]. This finding justifies the concerns that the WHO had on the potential impact of COVID-19 on the food and nutrition situation of the vulnerable groups, especially in developing countries [26].…”
Section: Resultssupporting
confidence: 77%
“…This is indicative that the majority (83.6%) of the farming households were food insecure. These results corroborate the findings reported by Toluwase et al [23] on the food insecurity status of rural households in the study area.…”
Section: Food Insecurity Status Of the Farming Householdssupporting
confidence: 93%
“…The farming households have a mean size of 6 members. This finding is similar to the average household size of farming households reported by Toluwase et al [23]. The result further suggests that farming households with the average household size could leverage family labor for carrying out various farm operations.…”
Section: Socioeconomic Characteristics Of the Farming Householdssupporting
confidence: 88%
See 1 more Smart Citation